Development of social anxiety cognition scale for college students: Basing on Hofmann’s model of social anxiety disorder - Zha, Yuxin; Tang, Qin; Jin, Xiaoru; Cai, Xinfei; Gong, Wen; Shao, Yongcong; Weng, Xiechuan (Frontiers in Psychology, 2023)
Introduction To develop the Chinese version of the Social Anxiety Cognition Scale for College Students (SACS-CS) based on Hofmann’s model of social anxiety disorder and examine its reliability and validity. Methods Based on literature analysis and structured interviews, a theoretical model was constructed and behavioral examples were collected. According to the results of participants’ and experts’ evaluations, the initial SACS-CS was developed. The study data were collected from a total of 500 valid participants, randomly divided into two samples. Sample 1 (n = 200) and sample 2 (n = 300) were considered for exploratory factor analysis and confirmatory factor analysis (CFA), respectively. Internal reliability and validity were examined using all 500 participants, and temporal reliability was established using sample 3 (n = 70), who completed the scale again after 4 weeks. Results The SACS-CS consists of 21 items, grouped under four factors: self-perception, social skills, emotional control, and cost estimation. The four-factor model fits well. The internal consistency coefficient of the scale and the four factors ranged from 0.87 to 0.96, and the test–retest reliability ranged from 0.76 to 0.84. The scores of the scale and the four factors were significantly correlated with the score of the Interaction Anxiousness Scale (r = 0.54–0.64). Discussion The SACS-CS possesses good reliability and validity and can be applied in the cognitive assessment of college students’ social anxiety. The scale could help people with different social anxiety disorder conditions receive more personalized interventions.